THE IMPACT OF LANGUAGE LEARNING ON BRAIN DEVELOPMENT AND MEMORY - Egamberdiyeva Nigina Sherzod qizi, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Language learning has a significant impact on brain development and memory improvement. This paper examines how acquiring a new language stimulates different areas of the brain and enhances cognitive functions. Studies show that learning a second language strengthens memory, improves attention, and increases the brain’s ability to process and store information. It also helps develop problem-solving skills and mental flexibility, as learners constantly switch between languages and adapt to new linguistic structures. Furthermore, bilingual and multilingual individuals often demonstrate better concentration and delayed cognitive decline compared to monolinguals. Language learning also encourages the formation of new neural connections, which supports long-term brain health. Therefore, this paper highlights the important role of language learning in enhancing memory capacity and promoting overall brain development.